2004
DOI: 10.1016/j.meegid.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of trypanosomes in Glossina pallidipes and G. longipennis in Kenya

Abstract: The polymerase chain reaction (PCR) was used to identify trypanosomes in Glossina pallidipes and G. longipennis caught in Kenya. Of 3826 flies dissected, 188 (4.9%) were parasitologically positive overall. The infection rate in G. pallidipes was 5.7% (187 of 3301 flies), but only one of 525 G. longipennis was infected (infection rate 0.2%). There was a higher infection rate in female G. pallidipes flies than male flies (chi(2) = 18.5, P < 0.001) and odds ratio = 2.5 (95% 1.6, 3.7). The infected flies were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Lack of detection of Kenyan T. vivax using PCR primers derived from a West African isolate indicates the widespread occurrence of genetic variants of this species (Njiru et al 2004), a fact corroborated in this study by the failure of the PCR based on SL gene sequences of South American/West African T. vivax (Ventura et al 2001) to detect the East African isolate examined in this study. Other distinct genetic variants of T. vivax may well exist, for example that represented by a partial SSU rRNA sequence amplified directly from tsetse collected in Tanzania, East Africa (Malele et al 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Lack of detection of Kenyan T. vivax using PCR primers derived from a West African isolate indicates the widespread occurrence of genetic variants of this species (Njiru et al 2004), a fact corroborated in this study by the failure of the PCR based on SL gene sequences of South American/West African T. vivax (Ventura et al 2001) to detect the East African isolate examined in this study. Other distinct genetic variants of T. vivax may well exist, for example that represented by a partial SSU rRNA sequence amplified directly from tsetse collected in Tanzania, East Africa (Malele et al 2003).…”
Section: Discussionsupporting
confidence: 70%
“…In our analysis, we picked out four isolates that had been previously categorised as single infections to be mixed infections. Direct sequencing of these products showed that KETRI 2729 contained a T. vivax [not the West African type because it was negative with TVW1 and TVW2, Masiga et al (1992) but positive with universal T. vivax primers (Masake et al 1997;Morlais et al 2001] (Mugittu et al 2000), while triple and quadruple infections may be a rare occurrence in animals, although common in tsetse flies (Njiru et al 2004). The use of universal tests for pathogenic trypanosomes would reduce the cost of PCR three to five times as the number of reactions required per sample would be reduced to one (Desquesnes and Davila 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Further, characterised trypanosome DNA from tsetse samples that had been analysed previously were included in this study (Njiru et al 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and snake has been documented previously (Waiswa et al, 2006;463 Bouyer et al, 2007;Farikou et al, 2010) and is further corroborated 464 by our data. Recently, several new trypanosome species or genotypes have 489 been discovered in tsetse flies (Adams et al, 2006(Adams et al, , 2010b498 Our nested 18S rRNA-based PCR assay proved to be highly sen- (Njiru et al, 2004;Hamilton et al, 2008;Adams et al, 2010a,b;511 Simo et al, 2012). Our findings further increase this diversity: Trypanosomes were detected by PCR only in the thorax and abdomen.…”
mentioning
confidence: 99%